Svoboda ustanavljanja v povezavi s čezmejnim prenosom statutarnega sedeža družb v EU in vpliv zadeve Polbud - Kotnik, Maja (Podjetje in delo, 2021)
The freedom of establishment is one of the fundamental rights specified in the Treaty on the Function of the European Union. It is the freedom given by the European Union to persons to carry out cross-border economic activity across member states. The freedom of establishment grants subjects the opportunity to enjoy free movement of goods, capital, services, and labour, also known as the "four freedoms", helps to provide economic prosperity and greater liberalisation in the common market of the European Union. The freedom of establishment is specified in articles of the Treaty on the Function of the European Union (Articles 49 to 55), but it is far more than just these plain articles. These articles are supplemented and completed by the case law of the Court of Justice of the European Union, which by its own case law follows the needs of economic prosperity and strives towards greater liberalisation. Over the years, the Court of Justice of the European Union has with its rulings broadened the boundaries of freedom of establishment as well as added new aspects. The Court of Justice of the European Union has ruled on several cases regarding the freedom of establishment, from the Segers case to the Cartesio case. The Court of Justice of the European Union was less liberal in older rulings compared to recent rulings. In the spirit of economic progress, the Court of Justice of the European Union has taken a great leap forward in its recent rulings. The 2017 Polbud case ruling, which was upgraded through the prior Cartesio, National Grid Indus and Vale cases, added a new important aspect to the freedom of establishment. Which is that, in addition to all the pre-existing aspects, the freedom of establishment includes the cross-border transfer of only the company's registered office across the European Union.
Keywords: 49. člen PDEU; 54. člen PDEU; Article 49 TFEU; Article 54 TFEU; cross-border transfer of company's registered office; čezmejni prenos statutarnega sedeža; freedom of establishment; Polbud; svoboda ustanavljanja